Building resilient microservices - Indrasiri, Kasun (O'Reilly Media, 2019)
"Building intermicroservice communication over the network is one of the hardest things in building microservices. The resiliency of microservice-based applications heavily depends on how well they handle interservice communication over an unreliable network. To make microservices resilient, the developers have to apply numerous resiliency patterns such as timeout, retry, circuit breaker, fail-fast, bulkhead, transactions, and failover/load balancing. Most of these patterns are implemented as part of the service logic, and microservice development technologies have to cater to such requirements. On the other hand, service meshes try to offer such commodity features as part of a shared communication infrastructure. Kasun Indrasiri (WSO2) explores the importance of microservice resiliency; details resilience patterns for interservice communication, including timeout, retry, circuit breaker, fail-fast, bulkhead, transactions, and failover/load balancing; dives into transactions resiliency; discusses technologies for building resilient microservices; and outlines the role service meshes play in building resilient microservices communication."--Resource description page